Evaluation of a Structuralized Sick-Leave Programme Compared with usual Care Sick-Leave Management for Patients after an Acute Myocardial Infarction - Lars Tjessum; Stefan Agewall (Medical Journals Sweden, 2023)
Objective: To compare a structuralized sick-leave programme with usual care sick-leave management in patients after an acute myocardial infarction. We hypothesize that a structured sick-leave programme will yield a faster return to work without negatively affecting quality of life. Methods: Patients admitted to Oslo University Hospital due to an acute myocardial infarction were included in the study. Patients were randomized into an intervention group or a conventional care group. Patients randomized to the intervention group were provided with a standard programme with full-time sick leave for 2 weeks after discharge and then encouraged to return to work. The sick leave of the conventional group was mainly managed by their general practitioner. Results: A total of 143 patients were included in the study. The conventional care group had a mean of 20.4 days absent from work, while that of the intervention group was significantly lower, with a mean of 17.2 days (p < 0.001) absent. There was no significant change in quality of life between the groups. Conclusion: These findings strengthen the case for structuralized follow-up of patients with acute myocardial infarction, as this will have positive economic consequences for the patient and society as a whole, without making quality of life worse. Further investigation, with a larger study population, is warranted to determine the extent of health benefits conferred by early return to work. LAY ABSTRACT This study aimed to compare a structuralized sick-leave programme with usual care sick-leave management in patients after an acute myocardial infarction. The study included 143 patients who were admitted to Oslo University Hospital due to an acute myocardial infarction. Patients were randomized to an intervention group or a conventional care group. The intervention group followed a standard programme with full-time sick leave for 2 weeks after discharge, and were then encouraged to return to work. Intervention group patients had access to a telephone number to contact a cardiologist for advice if needed. The sick leave of the conventional group was mainly managed by their general practitioner. The sick leave of the intervention group was, 3.2 days shorter, whereas there was no difference in quality of life between the groups. In conclusion, these results indicate potentially large positive economic consequences of a structuralized sick-leave programme for patients and for society as a whole, with no worsening in quality of life.